2018
DOI: 10.1111/1742-6723.13122
|View full text |Cite
|
Sign up to set email alerts
|

Is it time for a culture change? Blood culture collection in the emergency department

Abstract: BCs are a common investigation in the ED with a high false-positive rate. Strategies are required to reduce false positives, including reducing inappropriate collection and improving collection techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 5 publications
0
13
2
Order By: Relevance
“…2 Around 11%-15% of collected BCs are positive and studies show that up to half of those are false positives through contamination. [4][5][6] These…”
Section: Introductionmentioning
confidence: 99%
“…2 Around 11%-15% of collected BCs are positive and studies show that up to half of those are false positives through contamination. [4][5][6] These…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, real-life use of MS procedures often result in a low number of BC collection. A single BC set (i.e., culture of only 2 bottles also named solitary BC) is obtained in up to 41% to 94% of patients when MS procedure is used [ 1 , 13 , 14 ]. Another concern with the MS procedure is the rapid and significant loss of pathogen detection after initiation of antibiotic therapy [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“… 3 The percentage of true-positive blood cultures, disregarding contamination, ranges from 1.4% to 12.2% in ED populations worldwide. 4 , 5 , 6 , 7 , 8 , 9 , 10 Due to these low yields, blood culture outcomes affect treatment decisions in only 0.18–2.8% of patients presenting to the ED with suspected infection. 4 , 5 …”
Section: Introductionmentioning
confidence: 99%
“…A substantial 40–55% of positive cultures can be contaminated. 5 , 6 , 8 , 9 , 12 Three decades of research on this topic has consistently shown that contamination is associated with additional resource use (laboratory and microbiological testing), increased use of antibiotics, prolonged hospital stay, and even increased in-hospital mortality. 9 , 12 , 13 , 14 …”
Section: Introductionmentioning
confidence: 99%